The Relationship between 'Luxembourg' and European and national administrative bodies. Issue 6 (19th September 2018) - Krämer-Hoppe, Rike U.
ABSTRACT: In the Europeanisation literature, the fact that judgements of the European Court of Justice of the European Union (CJEU) can have an impact on national politics is no longer controversial. The paper shifts the focus towards administrative bodies and asks about the impact of CJEU case law on them. It establishes three different possible categories to describe the relationship between judicial politics and European and national administrative bodies: dialogue, subordination and indifference. The paper argues that access to courts is one crucial factor for a dialogical relationship. In contrast to the European Commission, national administrative bodies are less equipped to engage with the CJEU. The case study on social and environmental considerations in German public procurement decisions demonstrates that the relationship between national administrative bodies and the CJEU might be best described as one of indifference. National administrative bodies' focal point is mainly the national implementation of EU law.